Integrated hydrothermal evolution of a Botucatu paleodune and a blanketing lava flow from the Serra Geral Group, Uruguaiana - Leo Afraneo Hartmann; Felipe Padilha Leitzke; Cassiana Roberta Lizzoni Michelin; Melissa Johner; Cristiano de Carvalho Lana (Brazilian Journal of Geology)
Abstract The integrated hydrothermal evolution of the large Santa Otília Paleodune from the Botucatu paleoerg and the cover Catalán Flow from the Serra Geral Group is here evaluated in Uruguaiana, southern Paraná Basin. Methods included satellite images, field surveying, petrography, and U-Pb geochronology of detrital and volcanic zircon. The tops of the compound linear-barchan paleodunes are exposed in the topographic highs. Rhombi and bowls at the top of the silicified sandstone units are significant, as is the poor preservation of eolian layering. The fishbone-shaped dune tops are surrounded by the lavas. The oxidized top of the flow (upper Tier 2) overlies the reduced base (Tier 1), which consists of exposed, massive rocks in creek beds that are light gray-colored and contain small (10 cm) agate geodes and numerous silicified sandstone dikes. The youngest dated zircon grains from the sandstone are 225–300 Ma old (one 175 Ma age), and the main older age peaks are 450–600 Ma (predominant), 900–975 Ma, 1800–1900 Ma, and 2500 Ma; few Archean 2.5 Ga ages. The strongly altered volcanic zircon preserved in the reddened Catalán Flow yields a concordia-intercept age of 137.3 ±7.6 Ma. Complex processes are thus constrained in the evolution of the Botucatu Formation and the first Serra Geral lava flow.